Role of the gut in the pathophysiology of extrahepatic biliary obstruction. Issue 4 (October 1996) - Clements, W D; Parks, R; Erwin, P; Halliday, M I; Barr, J; Rowlands, B J
Abstract : BACKGROUND: Gram negative septic events are the commonest source of morbidity and mortality as a result of surgery in jaundiced patients. The large intestine provides the major source of Gram negative bacteria in mammals and is implicated in the pathogenesis of systemic endotoxaemia in obstructive jaundice. Bile salts have an important part in maintaining indigenous microecological homeostasis through their emulsifying properties. AIMS: The aim was to investigate the effects of biliary obstruction and isolated external biliary diversion on gastro-intestinal structure and caecal bacterial flora in relation to bacterial translocation. METHOD: Six groups of adult male Wistar rats were studied (no operation, sham operated, and bile duct ligated (BDL) for one and three weeks and a choledocho-vesical fistula (CDVF) for one week). At the end of the study period plasma was assayed for evidence of endotoxaemia and the animals were tested for bacterial translocation to the mesenteric lymph node complex (MLNC), liver, lungs, and spleen. Quantitative and qualitative bacteriological studies were performed on the caecal contents and segments of colon and terminal ileum were washed and prepared for histological assessment. RESULTS: Bacterial translocation was significantly increased in the BDL1 (68.8%) and BDL3 (60%) groups compared with the sham1 (6.3%), sham3 (9.1%), No operation (0%), and CDVF1 (16.7%) groups. Although translocation was more pronounced in the BDL1 group, this was almost exclusively to the MLNC compared with the more widespread translocation to other organs in the BDL3 group. The BDL3 group was the only group with significantly raised concentrations of endotoxin and anticore glycolipid. The caecal Gram negative aerobic counts were significantly increased in the BDL1 and CDVF1 groups compared with all other groups. There was evidence of structural abnormalities in the terminal ileum of rats jaundiced for three weeks, but not in the other groups. CONCLUSIONS: Biliary obstruction for one and three weeks promotes bacterial translocation although the mechanisms may be different. Absence of intralumenal bile results in a significant but self limiting increase in the Gram negative aerobic population, which may account for translocation in the early stages of biliary obstruction. As the duration of biliary obstruction increases systemic endotoxaemia is a consistent feature which, combined with factors such as immunological depression and physical disruption of gut barrier function, may promote bacterial translocation perpetuating systemic sepsis.